Identification of a Polar Region in Transmembrane Domain 6 That Regulates the Function of the G Protein-Coupled α-Factor Receptor - Dube, Peter (American Society for Microbiology, 1998)
The α-factor pheromone receptor (Ste2p) of the yeast Saccharomyces cerevisiae belongs to the family of G protein-coupled receptors that contain seven transmembrane domains (TMDs). Because polar residues can influence receptor structure by forming intramolecular contacts between TMDs, we tested the role of the five polar amino acids in TMD6 of the α-factor receptor by mutating these residues to nonpolar leucine. Interestingly, a subset of these mutants showed increased affinity for ligand and constitutive receptor activity. The mutation of the most polar residue, Q253L, resulted in 25-fold increased affinity and a 5-fold-higher basal level of signaling that was equal to about 19% of the α-factor induced maximum signal. Mutation of the adjacent residue, S254L, caused weaker constitutive activity and a 5-fold increase in affinity. Comparison of nine different mutations affecting Ser(254) showed that an S254F mutation caused higher constitutive activity, suggesting that a large hydrophobic amino acid residue at position 254 alters transmembrane helix packing. Thus, these studies indicate that Gln(253) and Ser(254) are likely to be involved in intramolecular interactions with other TMDs. Furthermore, Gln(253) and Ser(254) fall on one side of the transmembrane helix that is on the opposite side from residues that do not cause constitutive activity when mutated. These results suggest that Gln(253) and Ser(254) face inward toward the other TMDs and thus provide the first experimental evidence to suggest the orientation of a TMD in this receptor. Consistent with this, we identified two residues in TMD7 (Ser(288) and Ser(292)) that are potential contact residues for Gln(253) because mutations affecting these residues also cause constitutive activity. Altogether, these results identify a new domain of the α-factor receptor that regulates its ability to enter the activated conformation.